A study on the corrosion processes of eutectic Bi-42Sn solder alloy - Nam, Nguyen Dang (Vietnam Journal of Science and Technology, 2015)
The change of impedance in the passive, repassive states together with initial pitting process of eutectic Sn-Bi alloy is studied. Anodic polarization measures the passive, pitting, and repassive states to utilize the actual results and to assure the accuracy of the impedance results. X-ray photoelectron spectroscopy indicates that Sn oxides interact with Bi oxides to form a passive film. The dissolution of Bi accounts for the initial pitting and Sn oxides form the repassive film.